Process for Developing, Tracking and Reporting of Management Responses to Evaluations - CGIAR (CGIAR, 2024)
This document defines the roles and responsibilities related to developing, tracking, and reporting on Management Responses to evaluations and aligns with the requirement to prepare and submit Management Responses to Evaluations commissioned by the System Council,1 outlined further in the CGIAR Evaluation Policy (2022) and the accompanying guideline entitled, Management Engagement and Response: Process and Performance Evaluations in CGIAR (2023).